SKEMA KOMISI AFFILIASI DALAM E-COMMERCE: SOLUSI AKAD MUAMALAH PADA SHOPEE AFFILIATOR - Masyhudi, Habib (MIYAH : Jurnal Studi Islam, 2024)
Abstract: The form of muamalah business is very varied as well as affiliate programs. Shopee affiliate is a program that aims to increase the promotion of a number of stores in the Shopee marketplace. By promoting a number of links or product links from stores on Shopee on a number of applications and social media. However, in practice, it is widely found that the selling price of products can change. The unilateral price change resulted in shopee affiliates not knowing for sure the commission they would get. If the affiliate commission is equated with wages in Ijarah, then it makes the commission punished invalid because the wage conditions in ijarah must be clear and known in advance by both parties. The Ju'alah contract is a non-binding contract, so it can be canceled. Meanwhile, the scholars of Shafi'iyah and Hanabilah are of the opinion that it is permissible for ja'il to increase or decrease wages, because Ju'alah is a non-binding contract, so it is permissible to increase or decrease wages. Keywords: Commission, Shopee Affiliates, Ijarah, Jualah.